PERBANDINGAN INTENSITAS PEWARNAAN EKSTRAK BUAH TERUNG BELANDA (SOLANUM BETACEUM CAV) DENGAN DISCLOSING SOLUTION SEBAGAI BAHAN IDENTIFIKASI PLAK GIGI - Tri Yoga Suhedi; Hafni Bachtiar; Hidayati Hidayati (Andalas Dental Journal, 2014)
Plaque control is a procedure to prevent plaque accumulation on tooth surface that can be done with mechanic or chemical procedure. Using of mouthwash is an example of plaque control in chemical procedure. In this experiment, sunflower seed oil was used for mouthwash because it’s compositions have activity toward plaque forming microorganisms. This study was meant to know the effect of sunflower seed oil on reducing dental plaque index. This study was a clinical experimental study using pretest and postest control group design. The samples of this study were the students of MA PGAI Padang. 30 students were divided randomly into two groups, a control group and a test group. The test group were given sunflower seed oil, and control group were given aquadest . Dental plaque score was measured with PHP index before and after intervention. The data analyzed by computer program with independent sample t-test and its significancy accepted if p<0,05. The results showed the significant differences of plaque index decrease after intervention, 0,66 for the control group and 1,26 for the test group. It can be conclude that gargling with sunflower seed oil can decrease the plaque index.